Prevention and management of aggressive behaviour in patients at psychiatric hospitals: a document analysis of clinical practice guidelines in Hong Kong - Lantta T; Varpula J; Cheung T; Wong WK; Cheng PYI; Ng T; Ng CF; Yam CP; Ip G; Bressington DI; Valimaki M (WILEY, 2022)
Patient aggressive behaviour remains a significant public health concern worldwide. The use of restraint and seclusion remains a last resort but not an uncommon practice in clinical psychiatry in the management of aggressive events. There seems to be a paucity of evidenced-based research examining the policy framework guiding the use of restraint and seclusion in Asia contexts. The purpose of this study was to conduct an analysis on the guidelines in psychiatric hospitals in Hong Kong, and to explore the extent to which these guidelines were aligned with the international clinical guidelines for the prevention and management of patient aggression in psychiatry. A descriptive document analysis was used to analyse the guidelines from four psychiatric hospitals in Hong Kong in comparison with the NICE (National Institute of Health and Care Excellence UK) guidelines. Data were collected from December 2017 to June 2018. A total of 91 written documents were retrieved. Preventing violence and aggression has the highest level of agreement (31%,) while the use of restrictive interventions has the lowest level of agreement (12%). The sub-recommendation with most in line with the NICE guidelines were restrictive interventions, de-escalation, and improving service users' experiences. However, for example, staff training, working with police, and reduced use of restrictive interventions seemed to have no agreement with the NICE guidelines. Variation exists between the Asian (Hong Kong) local policy framework/guidelines and the European (UK) national policy framework. There are also large discrepancies in the written guidelines on patient aggressive behaviour when comparing local policy frameworks, cluster-based documents, and departmental practices.